Placental pathological findings in coronavirus disease 2019: Perinatal outcomes. (October 2022) - Arcos Júnior, Gelson Farias; Francisco, Rossana Pulcineli Vieira; Kill, Beatriz; Peres, Stela Verzinhasse; Gibelli, Maria Augusta B.C.; Ibidi, Silvia Maria; Carvalho, Werther Brunow de; Simões, Angelica Braz; Brizot, Maria de Lourdes; Schultz, Regina; Carvalho, Mariana Azevedo
Abstract: Introduction: Placental alterations caused by severe acute respiratory coronavirus-2 (SARS-CoV-2) infection have already been described, but most studies used small sample groups and the difference according to the severity of the disease has not been verified. Our objective was to describe placental alterations in patients with coronavirus disease 2019 (COVID-19) and analyze the association of pathological placental findings with the clinical parameters of COVID-19 and perinatal results. Methods: This was a nested study within a prospective cohort study involving 109 symptomatic pregnant women with COVID-19. The prevalence of observed placental alterations was described, and the associations of pathological findings with the clinical parameters of COVID-19 severity and with perinatal outcomes were assessed. Results: The frequency of types of placental features was poor maternal vascular perfusion in 45% of cases, poor fetal vascular perfusion in 33.9%, hematogenous origin infection in 32.1%, and morphological changes corresponding to ascending infection in 21.1%. Hematogenous infection differed significantly according to COVID-19 severity (p = 0.008), with a prevalence ratio (PR) of 1.74 (95% confidence interval, 1.02–2.98) in the moderate COVID-19 group compared to the mild COVID-19 group. Among the perinatal outcomes, there was an unexpected inverse association between prematurity and placental infection of hematogenous origin, with lower rates of prematurity among cases with inflammation of hematogenous origin (p = 0.029). Discussion: Moderate SARS-Cov-2 infection presented a higher prevalence of placental pathological findings. There was no association of placental findings with adverse perinatal outcomes. Highlights: The severity of COVID-19 infection is associated with different placenta features. Moderate COVID-19 has a higher prevalence of placental histological findings. Placental findings in COVID-19 were not associated with adverse perinatal outcomes.